Intimate partner violence identified through routine antenatal screening and maternal and perinatal health outcomes - Karina Chaves; John Eastwood; Felix A. Ogbo; Alexandra Hendry; Bin Jalaludin; Sarah Khanlari; Andrew Page (BMC, 2019)
ABSTRACT Background This study investigated the association between intimate partner violence (IPV) identified on routine prenatal screening and perinatal outcomes for mother and infant. Methods Routinely collected perinatal data for a cohort of all women and their infants born in public health facilities in Sydney (Australia) over the period 2014-2016 (N = 52,509) were analysed to investigate the risk of adverse maternal and perinatal outcomes associated with a history of IPV. The association between an affirmative response on prenatal IPV screening and low birth weight (LBW) < 2.5 kg, preterm birth < 37 weeks, breastfeeding indicators and postnatal depressive symptoms (PND) was investigated in a series of logistic regression models. Results IPV was associated with an increased risk of PND (OR = 2.53, 95% CI 1.76-3.63), not breastfeeding at birth (OR = 1.65, 95% CI 1.30-2.09), non-exclusive breastfeeding at discharge (OR = 1.66, 95% CI 1.33-2.07) and first post-natal visit (OR = 1.54, 95% CI 1.24-1.91). Self-reported fear of a partner was strongly associated with an increased risk of PND (OR = 3.53, 95% CI 2.50-5.00), and also LBW (OR = 1.58, 95% CI 1.12-2.22), preterm birth (OR = 1.38, 95% CI 1.08-1.76), lack of early initiation of breastfeeding (OR = 1.67, 95% CI 1.28-2.17), non-exclusive breastfeeding at discharge from hospital (OR = 1.60, 95% CI 1.24-2.06) and at the first post-natal visit (OR = 1.27, 95% CI 0.99-3.04). Conclusions IPV reported at the time of pregnancy was associated with adverse infant and maternal health outcomes. Although women may be disinclined to report IPV during pregnancy, universal, routine antenatal assessment for IPV is essential for early identification and appropriate management to improve maternal and newborn health.